Solid-State Physics An Introduction to Principles of Materials Science - Ibach, Harald. (Springer Berlin Heidelberg : Imprint: Springer, 2009)
This new edition of the popular introduction to solid-state physics provides a comprehensive overview on basic theoretical and experimental concepts of material science. Additional sections emphasize current topics in solid-state physics. Notably, sections on important devices, aspects of non-periodic structures of matter, phase transitions, defects, superconductors and nanostructures have been added, the chapters presenting semi- and superconductivity had been completly updated. Students will benefit significantly from solving the exercises given at the end of each chapter. This book is intended for university students in physics, engineering and electrical engineering. This edition has been carefully revised, updated, and enlarged. Among the key recent developments incorporated throughout GMR (giant magneto resistance), thin-film magnetic properties, magnetic hysteresis and domain walls, quantum transport, metamaterials, and preparation techniques for nanostructures. From a review of the original edition <U+0013> "... An excellent mix of concepts, theoretical arguments, and discussion of modern experiments - all at an introductory level ... Full of illustrations, photographs, schematic diagrams of experimental techniques, and graphs of results..." -- American Journal of Physics